CATALYZING METEOROLOGICAL INSIGHTS WITH A COST-EFFECTIVE WEATHER MONITORING SYSTEM - Alam, Ariful; Muntaha, Sidratula; Munshi, Poonam; Khan, Israt; Islam, Rakibul; Bhuian, Jamil; Arafat, Md.Yasir; Hasan, Md. Ridwanul (UI Scholars Hub, 2024)
Undoubtedly, one of the biggest alarming phenomena of this decade is the tremendous fluctuations in the weather and climate. Therefore, different types of surveys, investigations, and research are required in this regard in every region. A low-cost weather monitoring system can be implemented in every educational and research institute to collect and analyze different types of weather-related data. This study establishes the method of developing such a system and analyzing data in a simplified way which the data gathered during thunderstorms and cyclonic activity in Bangladesh. The system was designed with Proteus 8 professional software and developed by using a microcontroller, a temperature-humidity sensor, a wind speed analyzer, an automated rainfall analyzer, a barometric pressure sensor, and an LDR-based lightning bolt analyzer with a Linux-operated computer. The result obtained from the developed system is calibrated and compared with the standard value or theoretical value. The comparison graph shows that the developed system is efficient and reliable. After calibrating the system, several data points were collected at Mawlana Bhashani Science and Technology University, Tangail, Bangladesh. Developing an in-house weather monitoring system allows institutions to avoid costly foreign data purchases, reducing expenses and reliance on international services. Practically, this research can be applied to support climate studies and localized forecasting without the expense of high foreign exchange rates, allowing for more affordable meteorological research and enhancing local expertise.